The harridon paradox and new perceptions and methods of intrusions and firewalls / Mohd. Harridon Mohamed Suffian - Mohamed Suffian, Mohd. Harridon (2003)
Intrusions and firewalls are the norm in the computer system of today. This thesis listed old perceptions and methods of intrusion and firewall. The chosen intrusions are intrusion by means of ports, intrusion by means of SYN attack, intrusion by means of 'URG Flag' packets, and intrusion via web Contents. The main purpose of this thesis is to produce new perceptions and methods of the chosen intrusions stated above. The procreation of these new perceptions and methods leaded to the procreation of new firewall methods that were stated in this thesis. Another main proponent of this thesis is the creation of paradoxes particularly the Harridon paradox where the paradoxes would help the explanation of new perceptions and methods of intrusion and firewall. A new unit called "Harridon" was introduced. Mathematical equations and theories, logical and comparison techniques, association techniques, paradoxes, simplifying techniques, and "source code laid out" were used in order to gain the objective of producing new perceptions and methods of intrusion and firewall. It was found from this research that old perceptions and methods of intrusion and firewall were not adequate enough to sustain intrusions. This research will benefit the security entities by enhancing sepurities of computers or systems and deterring or eradicating intrusions.